Ambiguitas Hak Kebebasan Beragama di Indonesia dan Posisinya Pasca Putusan Mahkamah Konstitusi - Syafi’ie, M. (Mahkamah Konstitusi Republik Indonesia, 2011)
Freedom of religion is one of the rights guaranteed in the 1945 and several regulations regarding human rights in Indonesia. In Article 28I paragraph 1 stated that the religious right is expressed as a right that can not be deducted under any circumstances, as well as the right to life, the right not to be tortured, the right to freedom of thought and conscience, freedom from enslavement, recognition as a person before law, and and the right not to be prosecuted on the basis of a retroactive law. As one of the rights that can not be reduced, then the religious right should apply universally and non-discrimination. Splitting ensures the right to religious freedom in the midst of violence in the name of religion encourage some NGOs and leaders of democracy to conduct a judicial review of UU No. 1/PNPS/1965 on the Prevention of Abuse and or blasphemy. Act shall be deemed contrary to the guarantee of freedom of religion that can not be reduced under any circumstances. In that context, the Constitutional Court rejected judicial review entirely, although there are dissenting opinion from one of the judges of the constitution. After the Constitutional Court decision, the identity of religious rights in Indonesia becomes brighter, which can be reduced and restricted. Decision of the Constitutional Court not be good news for the applicants, because the UU No. 1/PNPS/1965 are one tool for certain groups to justify violence in the name of contemporary religion.